Patterns of nationhood and saving the state in Turkey - Al, Serhun.
1 online resource.
Keywords: Patterns of Nationhood and Saving the State in Turkey tackles a theoretical puzzle in understanding the state policy changes toward minorities and nationhood. First by placing the state in the historical context of the international system and second by unpacking the state through analyzing intra-elite competition in relation to the counter-discourses by minority groups within the context of Ottoman Empire and Turkey. What explains the persistence and change in state policies toward minorities and nationhood? Under what conditions do states change their policies toward minorities? Why do the state elites reconsider the state-minority relations and change government policies toward nationhood? Adopting a comparative historical analysis with longitudinal insights, the book unpacks these research questions and builds a theoretical framework by looking at three paradigmatic policy changes (Ottomanism in the mid-19th century, Turkish nationalism in the early 1920s, and multiculturalism in Turkey in the early 2000s) toward minorities and nationhood across Ottoman Empire and Turkey since the early 19th century. The book is an important contribution to studies in ethnicity and nationalism, therefore it is an essential resource for students and scholars interested in the Comparative Politics, Ottoman Empire, Turkey and Middle East Studies.